Interaction of Proctoring and Student Major on Online Test Performance - Alessio, Helaine M; Malay, Nancy; Maurer, Karsten; Bailer, A. John; Rubin, Beth (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Traditional and online university courses share expectations for quality content and rigor. Student and faculty concerns about compromised academic integrity and actual instances of academic dishonesty in assessments, especially with online testing, are increasingly troublesome. Recent research suggests that in the absence of proctoring, the time taken to complete an exam increases significantly and online test results are inflated. This study uses a randomized design in seven sections of an online course to examine test scores from 97 students and time taken to complete online tests with and without proctoring software, controlling for exam difficulty, course design, instructor effects, and student majors. Results from fixed effects estimated from a fitted statistical model showed a significant advantage in quiz performance (7-9 points on a 100 point quiz) when students were not proctored, with all other variables statistically accounted for. Larger grade disparities and longer testing times were observed on the most difficult quizzes, and with factors that reflected the perception of high stakes of the quiz grades. Overall, use of proctoring software resulted in lower quiz scores, shorter quiz taking times, and less variation in quiz performance across exams, implying greater compliance with academic integrity compared with when quizzes were taken without proctoring software.